Going green without a silver spoon: how social processes within families influence proenvironmental behaviors in China - Liu, Meiting (fi=Turun yliopisto|en=University of Turku|, 2025)
ABSTRACT According to the Global Waste Management Outlook 2024, householders across the world generate over two billion tons of municipal solid waste every year. One of the most immediate negative consequences of human activities is the rise in global surface temperatures, which increased by 1.1 degree Celsius from 2011 to 2020 compared with the recorded temperatures from 1850 to 1900. The rise in temperature has led to major repercussions to the environment and everyday human life, including extreme weather events worldwide. Despite the global environmental crisis, China—like many developing countries—still faces a trade-off between economic growth and environmental preservation. Socioeconomic barriers, such as poverty, social inequality, and political corruption, remain significant obstacles in these countries, complicating efforts to prioritize sustainability. Against this backdrop, even when environmental policies are promulgated, their execution is often ineffective, hindering the establishment of proenvironmental practices as social norms. The urgency of the current environmental crisis pressures researchers to ponder on the following question: Is there a possibility for people to contribute something beneficial to the environment without normalized proenvironmental social practice? In this dissertation, I focus on adolescents’ proenvironmental behaviors (PEBs) in China, aiming to identify the motivators and barriers to PEBs during adolescence. Theoretically, this dissertation draws on post-materialist theory to explore the concept and moralization of PEBs as well as the sociocultural determinants of PEBs, including childhood socioeconomic status, intentions for social mobility, values, and consumer patterns. Empirically, the current studies include one set of national data from the Chinese General Social Survey, along with one set of self-collected crosssectional data and one set of self-collected longitudinal data, all sampled from adolescents aged 11–17 in Central China. Various statistical methods were employed, including correlational analysis, confirmatory factor analysis (CFA), structural equation modeling, ordinary least squares (OLS) regression, mediation analysis, moderation analysis, conditional process analysis, fixed-effects modeling, and mixed-effects modeling. The results revealed that PEBs were positively associated with intentions for social mobility, as well as both reciprocal and authoritarian filial piety. Conversely, PEBs were negatively associated with factors such as childhood socioeconomic status, the purchase of commercial insurance, materialism, and psychological entitlement. In closing, all the articles demonstrated that individuals can contribute to the environment even in the absence of normalized proenvironmental practices. More specifically, this dissertation offers new insights into PEBs within a non-Western context. It demonstrates that a more sustainable lifestyle can be achieved if individuals transform their consumption patterns, appreciate traditional values, and pursue meaningful life goals. KEYWORDS: proenvironmental behaviors, socioeconomic status, materialism, psychological entitlement, intention for social mobility, filial piety

TIIVISTELMÄ Global Waste Management Outlook 2024 -raportin mukaan kotitaloudet ympäri maailmaa tuottavat yli kaksi miljardia tonnia yhdyskuntajätettä vuodessa. Yksi näkyvimmistä ihmisen toiminnan kielteisistä seurauksista on maapallon keskilämpötilan nousu: vuosien 2011–2020 aikana lämpötila oli keskimäärin 1,1 celsiusastetta korkeampi kuin vuosina 1850–1900. Tämä lämpeneminen on jo aiheuttanut vakavia ympäristö- ja arkipäivän vaikutuksia, kuten lisääntyneitä äärimmäisiä sääilmiöitä eri puolilla maailmaa. Vaikka globaali ympäristökriisi on pahenemassa, Kiina — kuten monet muut kehittyvät maat — kamppailee edelleen talouskasvun ja ympäristönsuojelun yhteensovittamisen kanssa. Sosiaaliset ja poliittiset tekijät, kuten köyhyys, sosiaalinen eriarvoisuus ja poliittinen korruptio, vaikeuttavat kestävyyden asettamista etusijalle useissa maissa. Ympäröstöpoliittisten toimien täytäntöönpano on usein tehotonta, mikä estää ympäristöä edistävien käytäntöjen vakiinnuttamisen sosiaalisiksi normeiksi. Nykyisen ympäristökriisin kiireellisyys herättää tärkeän kysymyksen: voivatko ihmiset edistää ympäristön hyvinvointia, vaikka vakiintuneita ympäristömyönteisiä käytäntöjä ei olisi? Tässä väitöskirjassa tarkastellaan kiinalaisnuorten ympäristönsuojeluun tähtäävää käyttäytymistä (pro-environmental behavior, PEB). Nuoruusiässä ilmenevien PEB-motivaattorien ja -esteiden tunnistaminen voi auttaa kehittämään strategioita, joilla nuorten ympäristömyönteistä toimintaa vahvistetaan. Teoreettisesti tutkimus nojaa postmaterialistiseen teoriaan tutkiakseen PEB:n käsitettä, sen moralisaatiota sekä sosiokulttuurisia tekijöitä, kuten lapsuuden sosioekonomista asemaa, sosiaalisen liikkuvuuden tavoitteita, arvoja ja kulutustottumuksia. Empiirinen aineisto koostuu Kiinan yleisen sosiaalitutkimuksen (Chinese General Social Survey) kansallisesta aineistosta sekä kahdesta itse kerätystä aineistosta: poikittaistutkimuksesta ja pitkittäistutkimuksesta, jotka molemmat on kerätty 11–17-vuotiailta nuorilta Keski-Kiinassa. Analyyseissä hyödynnettiin useita tilastollisia menetelmiä, kuten korrelaatioanalyysiä, konfirmatorista faktorianalyysiä (CFA), rakenneyhtälömallinnusta, OLS-regressiota, mediaatio- ja moderaatioanalyysejä, ehdollista prosessianalyysiä sekä kiinteiden ja sekavaikutteiden mallinnusta. Tutkimuksen tulokset osoittivat, että PEB oli positiivisesti yhteydessä sosiaalisen liikkuvuuden tavoitteluun sekä vastavuoroiseen ja auktoriteettipohjaiseen perheen kunnioitukseen. Toisaalta PEB:llä oli negatiivinen yhteys lapsuuden sosioekonomiseen asemaan, kaupallisen vakuutuksen hankintaan, materialismiin ja psykologiseen erityisoikeuden tunteeseen. ASIASANAT: Ympäristön suojeluun tähtäävään käyttäytymiseen, sosioekonominen asema, materialismi, psykologinen erityisoikeuden tunne, sosiaalisen liikkuvuuden tavoittelu, perhehurskaus